Body image issues during pregnancy : an interpretive phenomenological analysis - Harding, Gizella (My University, 2021)
The physical changes that a woman undergoes during pregnancy may affect her body image and consequently, her emotional and psychological well-being. The purpose of this study was to develop a comprehensive understanding of the lived experiences of pregnant women and the effect of pregnancy on their self-image and subsequent emotional and psychological experiences. Eight women who had previously given birth or were pregnant were recruited as participants by employing snowball sampling. Semi-structured interviews were conducted to collect data. Interpretive phenomenological analysis was employed to analyse the data. The findings revealed that the majority of the participants generally experienced overall body satisfaction. However, their experience was largely influenced by the phase of pregnancy and relevant physical changes associated with the particular phase. Furthermore, the social comments they received had an influence on their experiences. The findings were also related to the social comparisons in which the participants tended to engage. Finally, it is recommended that future research be conducted on the experience of body image of pregnant women within the context of their culture, ethnicity and unique demographics given that culture influences ideas about ideal body shape and size. Future studies should include a more diverse sample. Keywords: Body image, objectification, self-objectification, social comparison
Thesis (M.A. (Clinical Psychology)) -- University of Limpopo, 2021
Keywords: Body image; Objectification; Self-objectification; Social comparison; Body image - Social aspects; Body image